PENERAPAN PENDEKATAN SAINS TEKNOLOGI MASYARAKAT (STM) PADA MATERI ASAM BASA TERHADAP ASPEK KESADARAN LINGKUNGAN, RESPON, DAN HASIL BELAJAR KIMIA SISWA SMK N 3 LUBUKLINGGAU - Yeni Trianah (Jurnal Perspektif Pendidikan, 2019)
This study aims to discuss the improvement of students' mathematical problem solving abilities through the (Laps-Heuristic) learning model. The method in this research is experiment with the creation of pretest and posttest groups. The population in this study were all students of class VIIIMTs Negeri 2 Muara Enim, and a sample of two classes would be taken, namely class VIII As many as 40 students as the experimental class who received the Laps-Heuristic learning model and class VIII B as many as 39 students as the control class who received conventional learning. . The instrument needed in this research is the Mathematical Problem Solving Ability test in the form of empirically validated essay questions. Data analysis used t test (Independent samples t test), by first testing for normality and homogeneity. Based on the data analysis, the results obtained in this study indicate that there is an effect of the (Laps-Heuristic) learning model on the improvement of students' mathematical problem solving abilities at MTs Negeri 2 Muara Enim.